Rekonstruksi Kebijakan Pembelajaran Deep Learning Dalam Pendidikan Agama Islam (Analisis Konseptual dan Implementatif di Era Transformasi Digital) - Syarif Hidayat (CV Edujavare Publishing, 2025)
This study aims to reconstruct deep learning policies in Islamic Religious Education (PAI) by analyzing theoretical concepts, curriculum policies, and implementation implications in the era of digital transformation. Using library research methods, this study examines various primary and secondary literature related to deep learning, PAI policies, and educational technology. The results of the study indicate that the concept of deep learning—as proposed by Marton & Säljö, John Biggs, and Thomas–Bain—is highly relevant to strengthening the quality of PAI learning, which emphasizes understanding meaning, reflection, critical analysis, and the application of religious values ​​in real life. The Independent Curriculum provides an ideal space through Learning Outcomes (CP), flexible teaching modules, and the Pancasila Student Profile Project (P5), but its implementation still faces obstacles such as the dominance of lecture methods, factual assessments, and low digital and in-depth pedagogical literacy among PAI teachers. Digital transformation presents significant opportunities through the use of Artificial Intelligence (AI), Big Data, Learning Analytics, and Learning Management Systems (LMS) that can create adaptive, collaborative, and contextual learning. However, disparities in digital literacy and the use of technology that has not yet addressed in-depth pedagogical aspects remain major challenges. This research recommends reconstructing Islamic Religious Education (PAI) policy through the integration of HOTS (Hot and Popular Culture), religious moderation, experiential Islamic learning, and strengthening teacher competencies in digital pedagogy and deep learning strategies.